-3(3y-8)+5y=4(y+7)

Simple and best practice solution for -3(3y-8)+5y=4(y+7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(3y-8)+5y=4(y+7) equation:


-3(3y-8)+5y=4(y+7)

We simplify the equation to the form, which is simple to understand
-3(3y-8)+5y=4(y+7)

Reorder the terms in parentheses
+(-9y+24)+5y=4*(y+7)

Remove unnecessary parentheses
-9y+24+5y=+4+*(+y+7+)

Reorder the terms in parentheses
-9y+24+5y=+(+4y+28)

Remove unnecessary parentheses
-9y+24+5y=+4y+28

We move all terms containing y to the left and all other terms to the right.
-9y+5y-4y=+28-24

We simplify left and right side of the equation.
-8y=+4

We divide both sides of the equation by -8 to get y.
y=-0.5

See similar equations:

| 6m^2-13m=28 | | 11x-6=2x+7 | | 7x^2+3x+4=1 | | y=0.75(100)+25 | | y=0.75(50)+25 | | x^2-5x+3= | | x+2(x+10)=167 | | 6y-4=2y+3 | | x=3x+13x^2+39 | | -(8x+3y+9)= | | 12+3s=42 | | x=3x+13x^2 | | -8x^2-6x-36=0 | | 6b^2-27b^1-15=0 | | 7(w+6)=-3w+2 | | 11n-(3n-7)= | | cos(6x)=-cos(4x) | | 3.8/44.08= | | -5v+3(v+5)=-3 | | 3=(-5x+16) | | x^2-2.4x+1.6=0 | | 11/3-x=76 | | 5(y+4)-7y=18 | | 3x+10=-20-2x | | y=0.40x+15 | | 9m+36=0 | | 7x-8=2x+11 | | 3(4x-2)=90 | | -5x-8x=78 | | 5y-13=37whatisy | | 14z^4+10z^3+4z^2= | | y+51=16 |

Equations solver categories